A need of time: Android Security - Prashant.V, Mr.; Devadiga, Mr. Nagendra; C.P, Mrs.Vandana. (IJRDO -Journal of Computer Science Engineering, 2016)
With millions of free applications on the Android Store, users are tempted to download these applications. These apps maybe games or any productive app like Antivirus or Office related apps. Smartphones have become a big essential to everyone’s life. Since user confidential data is accessed by these applications, the user security is at threat. In this paper, the various aspects of security attack in android is analyzed, particularly attacks using cameras.